An extra virgin olive oil‐enriched chocolate spread positively modulates insulin‐resistance markers compared with a palm oil‐enriched one in healthy young adults: A double‐blind, cross‐over, randomised controlled trial. Issue 2 (25th September 2021) - Tuccinardi, Dario; Di Mauro, Antonio; Lattanzi, Greta; Rossini, Giovanni; Monte, Lavinia; Beato, Ivan; Spiezia, Chiara; Bravo, Maria; Watanabe, Mikiko; Soare, Andreea; Kyanvash, Shadi; Armirotti, Andrea; et al.
Abstract: Aims: To investigate if extra virgin olive oil (EVOO) or palm oil enriched chocolate spreads consumption leads to different results in terms of plasma ceramides concentration, glucose and lipid metabolism, inflammatory markers and appetite regulation in young healthy subjects. Methods: In a 2‐week, double‐blind, cross‐over, randomised controlled trial, 20 healthy, normal‐weight subjects with a mean age of 24.2 years (SD: 1.2), consumed chocolate spread snacks (73% of energy [%E] from fat, 20% from carbohydrates and 7% from proteins), providing 570 Kcal/day added to an isocaloric diet. The chocolate spreads were identical, except for the type of fat: EVOO oil, rich in monounsaturated fatty acids (MUFAs), or palm oil, rich in Saturated Fatty Acids (SFAs). Results: EVOO‐enriched chocolate spread consumption led to better circulating sphingolipids and glucose profile, with reduced plasma ceramide C16:0, ceramide C16:0/ceramide C22:0‐ceramide C24:0 ratio and sphingomyelin C18:0 ( P = 0.030, P = 0.032 and P = 0.042, respectively) compared to the palm oil‐enriched chocolate spread diet. HOMA‐IR and plasma insulin were lower, while the Quicki and the McAuley Index were higher after the EVOO diet compared to the palm oil diet ( P = 0.046, P = 0.045, P = 0.018 and P = 0.039 respectively). Subjects maintained a stable weight throughout the study. No major significant changes in total cholesterol, triglycerides, HDL, inflammatory markers, and appetite‐regulating hormones/visual analogue scale were observed between the groups. Conclusions: Partially replacing SFAs with MUFAs in a chocolate‐based snack as part of a short‐term isocaloric diet in healthy individuals may limit SFAs detrimental effects on insulin sensitivity and decrease circulating harmful sphingolipids in young adults.